A dithienobenzothiadiazole-quaterthiophene wide bandgap polymer enables non-fullerene based polymer solar cells with over 15% efficiency. (26th October 2021) - Zhang, Zesheng; Pan, Feilong; Luo, Mei; Yuan, Dong; Liu, Haizhen; Liu, Qin; Wu, Zhuhao; Zhang, Lianjie; Chen, Junwu
Abstract: In this work, a wide bandgap (WBG) polymer donor PDT f BT-4T based on dithienobenzothiadiazole (DT f BT) and quaterthiophene (4T) was synthesized for the application in non-fullerene polymer solar cells (PSCs). Polymer PDT f BT-4T showed film absorption peak at 554 nm and optical band gap of 1.93 eV. Complementary absorption and sufficiently energetic offsets could be achieved between the PDT f BT-4T and a benzotriazole-fused Y-series non-fullerene acceptor Y14. The PDT f BT-4T:Y14 active layer could deliver an open-circuit voltage of 0.83 V, a short-circuit current density of 25.42 mA cm −2, and a fill factor of 72.0%, corresponding to a power conversion efficiency (PCE) of 15.19%. This is the highest efficiency among WBG polymer donors based on an electron-deficient unit and an oligothiophene, which is also significantly higher than those of the fluorinated or esterified polythiophenes. The results indicate that DT f BT is a powerful electron-deficient unit, which is promising in the construction of simple WBG polymer donors for efficient NFA based PSCs. Graphical abstract: Image 1 Highlights: Polymer donor derived from dithienobenzothiadiazole and quaterthiophene. A simple wide bandgap polymer donor enables an over 15% efficiency. Dithienobenzothiadiazole is an powerful electron-deficient unit.